2016
DOI: 10.1017/s1751731115002396
|View full text |Cite
|
Sign up to set email alerts
|

New insight of some extracellular matrix molecules in beef muscles. Relationships with sensory qualities

Abstract: The aim of this study was to highlight the relationships between decorin, tenascin-X and type XIV collagen, three minor molecules of extracellular matrix (ECM), with some structural parameters of connective tissue and its content in total collagen, its cross-links (CLs) and its proteoglycans (PGs). In addition, we have evaluated impact of these minor molecules on beef quality traits. The relative abundance of these molecules was evaluated by western blot analysis in Longissimus thoracis (LT) and Biceps femoris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Customer assessments on intrinsic quality attributes for beef products have a direct relationship with sensory attributes, visual characteristics and structural characteristics . Sensory profiling attributes are assessed by trained panellists using quantitative descriptive analysis (QDA).…”
Section: Literature On the Differences In Consumer Liking Of Beefmentioning
confidence: 99%
“…Customer assessments on intrinsic quality attributes for beef products have a direct relationship with sensory attributes, visual characteristics and structural characteristics . Sensory profiling attributes are assessed by trained panellists using quantitative descriptive analysis (QDA).…”
Section: Literature On the Differences In Consumer Liking Of Beefmentioning
confidence: 99%
“…From these properties and according to Bailey and Light [15], it has been suggested that these molecules could contribute to the meat texture. However, there is a scarcity in studies that addressed this question unless one work from our groups that studied the relation between decorin, tenascin-X, collagen XII and XIV and beef sensory properties [16]. According to our previous study, it seems important to study all these components together, in combination with total and insoluble collagen, as they would have complementary information and an additive role that would play on the final texture quality of meat.…”
Section: Introductionmentioning
confidence: 99%